Updates on bone health in children with gastrointestinal diseases - Hye Ran Yang (Korean Society of Pediatric Endocrinology, 2020)
Chronic gastrointestinal diseases such as inflammatory bowel disease, malabsorption syndromes (e.g., intestinal lymphangiectasia, celiac disease, congenital chloride diarrhea, cystic fibrosis), and postsubtotal gastrectomy state or short-bowel syndrome after extensive bowel resection are related to poor bone health in pediatric patients due to increased risks of low bone mineral density, osteoporosis, and fractures. The pathophysiology of abnormal bone health in pediatric gastrointestinal diseases may present from inflammation to malabsorption. In children with chronic gastrointestinal diseases at high risk of poor bone health, routine evaluation using dual-energy X-ray absorptiometry and appropriate prevention or treatment strategies are needed.